A rhizomatic exploration of a professional development non-linear approach to learning and teaching: Two teachers' learning journeys in 'becoming different'. (July 2022) - Scanlon, Dylan; MacPhail, Ann; Calderón, Antonio
Abstract: Drawing on rhizomatics and figurational sociology, the concept of 'assemblage', 'becoming', and a 'figuration' were used to explore learning and teaching, and specifically, how teachers negotiate their learning and teaching in becoming teachers of a new school subject. We argue a 'teacher assemblage' is an assemblage which takes place across multiple spaces and the elements within this assemblage change depending on the space that the teacher occupies. These collaborative negotiations within an assemblage highlight the complexity in the learning and teaching process and the ongoing process of 'becoming different' throughout the professional development and learning journey (and beyond).